(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2025)
The French campaign left Egypt after failing to achieve its goals and hopes of making Egypt a French colony. The Ottoman forces, the Mamluk beys, and the English joined forces with the Egyptians in expelling it. As a result, Egypt returned to the fold of the Ottoman Empire, which tried to regain its actual authority from the Mamluks, the real and actual authority over Egypt. It took many measures, the first of which was appointing a new Ottoman governor over Egypt, and plotting many conspiracies against the Mamluk beys and leaders to kill them or deport them outside the country. What helped the Ottomans was the profound impact that the French campaign had on the dispersion of the power of the Mamluk beys and leaders and their dispersion into competing parties in order to seize power in Egypt. They were unable to gather their forces to become a force with weight in directing matters in their favor and restoring their authority. The English and French also used them to achieve their ambitions and interests in the country, which led to the country entering a state of chaos and political instability that extended between the years (1801-1805 AD), and what indicates the extent of the political chaos is the succession of five Ottoman governors in ruling Egypt during this period, and Britain’s procrastination in remaining in Egypt, and France’s protest against its remaining in accordance with the terms of the Peace of Amiens, which led to the country entering a state of conflict and political chaos, focused primarily between (the Ottomans - the Mamluks - the people of the country) and secondarily with the French and the English, which ended with the emergence of the role of the local forces and the Egyptian people and their decision to remove the Ottoman governor Khurshid Pasha, and choose Muhammad Ali as governor of Egypt for what they saw of his justice and standing by the Egyptian people and his closeness to their scholars, and the Ottoman Sultanate’s submission to the people’s decision and its issuance of a decree confirming Muhammad Ali as governor of Egypt, whose era would be a new beginning in the history of Egypt.